Use of Information Education in Improving Competence of Information Teachers Information Technologies - Kadirov T; I.B, SettingsAminov (Indonesian Journal of Education Methods Development, 2020)
This article discusses the purpose of public education reforms in the country, the conditions that enable teachers of specific sciences to enhance the competence of information technology.